Contribution of Epithelial Cell Dysfunction to the Pathogenesis of Chronic Rhinosinusitis with Nasal Polyps. Issue 6 (November 2019) - Wynne, Michael; Atkinson, Carl; Schlosser, Rodney J.; Mulligan, Jennifer K.
Background: In the past, the airway epithelium was thought to be primarily an inert physical barrier. We now know that the upper airway epithelium plays a critical role in both innate and adaptive immunity, and that epithelial dysfunction is strongly associated with inflammatory airway disease. The pathogenesis of chronic rhinosinusitis is poorly understood, but growing evidence supports a key role for the airway epithelium in the pathophysiology of the disease. Objective: The purpose of this study is to explore our current understanding of how dysfunction in human sinonasal epithelial cells (HSNECs) contributes to the pathogenesis of chronic rhinosinusitis with nasal polyps (CRSwNP) and to examine how current and developing therapies affect epithelial cell functions. Methods: A literature review of papers published in English pertaining to epithelial cell dysfunction in patients with CRSwNP was performed using the PubMed database. The search utilized combinations of the following key words: sinusitis, polyps, epithelium, pathophysiology, barrier function, dendritic cells, eosinophils, T cells, complement, mucociliary clearance, vitamin D, cytokines, chemokines, taste receptors, steroids, saline, and therapy. Results: HSNEC mucociliary clearance, barrier function, secretion of cytokines, influence on dendritic cells, influence on T-cells, regulation of eosinophils, vitamin D metabolism, complement production, and taste receptor function are altered in patients with CRSwNP and contribute to the pathogenesis of the disease. Current therapies utilized to manage CRSwNP counteract the effects of HSNEC dysfunction and relieve key symptoms of the disease. Conclusion: HSNECs are key players in both innate and adaptive immunity, and altered epithelial functions are closely intertwined with the pathogenesis of CRSwNP. Our review supports further investigation of altered HSNEC function in patients with CRSwNP and supports development of novel epithelial-targeted therapies for its management.